Participatory Vulnerability Analysis Profile Updated 2021 - International Institute of Rural Reconstruction (International Institute of Rural Reconstruction, 2021)
The Participatory Vulnerability Analysis study was conducted in the 11 villages or barangays in Guinayangan Climate-Smart Village to provide a better understanding of the community and inform the project of the conditions and factors that affect their vulnerability to climate change impacts. This in turn will inform appropriate programs and actions that the community can carry out to prepare them cope with impacts and increase resiliency.